1997
DOI: 10.1021/np960608e
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cytotoxicity of Ginkgetin from Selaginella moellendorffii

Abstract: Bioassay-directed fractionation of an ethanolic extract of Selaginella moellendorffii has led to the isolation of a known biflavone, ginkgetin (1). A dose-dependent inhibition was observed with 1 on the growth of OVCAR-3 (human ovarian adenocarcinoma) cells with 50% inhibition occurring at 1.8 micrograms/mL. Nonbioactive fractions yielded four additional known biflavones, amentoflavone 7,4',7",4"'-tetramethyl ether, kayaflavone, podocarpusflavone A, and amentoflavone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 22 publications
2
65
0
1
Order By: Relevance
“…11,12 Moreover, many studies have suggested that flavonoids exhibit important cancer chemoprevention [13][14][15][16] and anticancer activities. [17][18][19] Focusing on the anti-cancer properties of chemical constituents from Brazilian plants we have assayed the cytotoxic activities against Ehrlich carcinoma and human K562 leukaemia cells of a glicoalkaloid fraction (GB), the flavonoid tiliroside (1), solasonine (2) and peracethyl solasonine (2a) from Solanum crinitum Lam and the aglicone solasodine (3) from S. jabrense. We report here our latest results.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Moreover, many studies have suggested that flavonoids exhibit important cancer chemoprevention [13][14][15][16] and anticancer activities. [17][18][19] Focusing on the anti-cancer properties of chemical constituents from Brazilian plants we have assayed the cytotoxic activities against Ehrlich carcinoma and human K562 leukaemia cells of a glicoalkaloid fraction (GB), the flavonoid tiliroside (1), solasonine (2) and peracethyl solasonine (2a) from Solanum crinitum Lam and the aglicone solasodine (3) from S. jabrense. We report here our latest results.…”
Section: Introductionmentioning
confidence: 99%
“…All experiments were carried out at least three times and they gave similar results. The inhibitory activities of ochnaflavone (4) and wogonin (reference compound) on COX-2 catalyzed PGE 2 production from LPS-activated RAW 264.7 cells were estimated. Ochnaflavone exhibited quite strong inhibitory activity (IC 50 = 1.08 μM) on COX-2 catalyzed PGE 2 production from LPS-activated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, certain biflavonoids were reported to inhibit phosphodiesterase, 1 lens aldose reductase, 2 mast cell histamine release 3 and to show anticancer activity. 4 Recently, some C-C and C-O-C biflavonoids were synthesized and their anti-microbial 5 and anti-inflammatory 6,7 activities were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…show notable anti-cancer properties (Lai et al, 2010). The antithiamin substances in brackens, such as astragalin, isoquercitrin, rutin, caffeic acid, and tannic acid have Lee and Lin, 1988;Silva et al, 1995;Sun et al, 1997;Lee et al, 1999;Lin et al, 2000;Su et al, 2000;Chen et al, 2005b;Gao et al, 2007;Li J et al, 2014;Li S 2014;Elda et al, 2015 35 Guha et al, 1996 MTT: 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (Konoshima et al, 1996). A. evecta and Selaginella tamariscina have been shown to have significant antidiabetic activity (Miao et al, 1996;Nguyen, 2005).…”
Section: Anti-cancer Antidiabetic and Antiviral Activitymentioning
confidence: 99%
“…3d), Selaginella lepidophyla, Selaginella labordei, Selaginella moellendorffii, Selaginella delicatula, S. tamariscina, and Sellaginella doederleinii (Fig. 3e) were shown to have cytotoxic and antimutagenic effects due to the presence of bioflavonoids (Lee and Lin, 1988;Silva et al, 1995;Sun et al, 1997;Lee et al, 1999;Lin et al, 2000;Su et al, 2000;Chen JJ et al, 2005;Gayathri et al, 2005;Woo et al, 2005;Gao et al, 2007;Shi et al, 2008;Tan et al, 2009), while Pteris semipinnata (Fig. 4c) and P. multifida have cytotoxic effects due to the presence of diterpenes (Woerdenbag et al, 1996;Li et al, 1998Li et al, , 1999.…”
Section: Anti-cancer Antidiabetic and Antiviral Activitymentioning
confidence: 99%